2017
DOI: 10.7554/elife.24414
|View full text |Cite
|
Sign up to set email alerts
|

Host-selected mutations converging on a global regulator drive an adaptive leap towards symbiosis in bacteria

Abstract: Host immune and physical barriers protect against pathogens but also impede the establishment of essential symbiotic partnerships. To reveal mechanisms by which beneficial organisms adapt to circumvent host defenses, we experimentally evolved ecologically distinct bioluminescent Vibrio fischeri by colonization and growth within the light organs of the squid Euprymna scolopes. Serial squid passaging of bacteria produced eight distinct mutations in the binK sensor kinase gene, which conferred an exceptional sele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 155 publications
(294 reference statements)
1
24
0
Order By: Relevance
“…Strikingly, all identified adaptive mutations for infection affect global regulatory proteins (HrpG, VsrA, EfpR, PhcA) controlling, positively or negatively, the expression of several hundreds of genes (Figure 3) [23,86,[89][90][91][92]. This is in accordance with other evolution experiments in which global regulators were frequently targeted [93][94][95][96][97]. Our results confirmed that mutations in global regulators can be highly beneficial by changing the expression of hundreds of genes in a concerted way, particularly during the first steps of adaptation to a new environment [98].…”
Section: Regulatory Rewiring Of the Recipient Genome As A Main Driversupporting
confidence: 86%
“…Strikingly, all identified adaptive mutations for infection affect global regulatory proteins (HrpG, VsrA, EfpR, PhcA) controlling, positively or negatively, the expression of several hundreds of genes (Figure 3) [23,86,[89][90][91][92]. This is in accordance with other evolution experiments in which global regulators were frequently targeted [93][94][95][96][97]. Our results confirmed that mutations in global regulators can be highly beneficial by changing the expression of hundreds of genes in a concerted way, particularly during the first steps of adaptation to a new environment [98].…”
Section: Regulatory Rewiring Of the Recipient Genome As A Main Driversupporting
confidence: 86%
“…Interestingly, in Cupriavidus taiwanensis, a Ralstonianeighboring taxon that evolved into Mimosa symbionts, the phcB and phcS orthologous genes were found under positive selection and associated with the transition to symbiosis during the natural evolution of this rhizobium species (29), likely reflecting the need to adjust QS to the legume endosymbiotic niche. Adaptive mutations altering QS responsiveness were also evidenced during experimental and natural evolution of other pathogenic and symbiotic bacteria such as Vibrio fischeri and Staphylococcus aureus (35)(36)(37)(38), exemplifying the role of these sensory systems in bacterial adaptation and phenotypic diversification. The role of QS in rhizobial symbiosis is, however, variable, either neutral (39), positive (40)(41)(42), or negative (43,44).…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, we note that the sypE frameshift is not present in SR5, arguing for distinct modes of biofilm regulation in groups A, B, and C. At the same time, this study provides evidence that some aspects of biofilm regulation are conserved in diverse squid symbionts, such as the effects of the strong biofilm negative regulator BinK. Published data indicate that evolved BinK alleles can alter colonization of H905 (group B) and MJ11 (group C), and that a deletion of MJ11 binK leads to enhanced colonization (20). Our experiments in Fig.…”
Section: Discussionmentioning
confidence: 53%
“…The entire colonization lifecycle likely requires a balance between biofilm formation/cohesion and biofilm dispersal, and these data argue that group A strains are more strongly tilted toward the biofilm-producing state. There is evidence that strains lacking BinK exhibit a colonization advantage in the laboratory (18,20), suggesting that this strategy of more readily forming biofilms provides a fitness advantage in nature. At the same time, the biofilm negative regulator BinK is conserved among V. fischeri strains examined (including MB11B1 [Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation